ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS V PADA MATERI KUBUS DAN BALOK - Ike, Fadillah; Suhendri, Huri (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
The research, which was conducted at MI Attaqwa 28 Bekasi City, aimed to describe the level of understanding of students' mathematical concepts on Cube and Block material. The research method used is descriptive qualitative research with the sampling technique used is purpose sampling. The subjects in this study were 32 students. Based on the results of research and data analysis that the ability to understand mathematical concepts of class V students on cube and block material is classified as a concept understanding percentage of 76%, and the average error made by students reaches 24%, which is low as much as 20 Subjects get a score of 75 representing the category high ability to understand mathematical concepts High ability students are able to master all indicators. A total of 12 subjects scored <75 representing the category of low mathematical concept understanding ability, unable to master all indicators, students were unable to explain systematic concepts and were unable to determine the steps in mathematical concepts